PENDIDIKAN KARAKTER PERSPEKTIF IBN QAYYIM AL-JAUZIYYAH DALAM KITABTUHFATU AL-MAUDUD BI AHKAMI AL-MAULUD - Meisy Permata Sari; Fajri Ismail; Muhammad Win Afgani (JURNAL PENDIDIKAN DAN KEGURUAN, 2023)
Research on early childhood character education according to Ibn Qoyyim al-Jauziyyah in the book Tuhfaul Maudud bi Ahkamil Maulud aims to understand the guidelines and principles presented by Ibn Qoyyim in shaping the character of early childhood. This study used content analysis methods to evaluate the content of the book Tuhfaul Maudud bi Ahkamil Maulud and found the main themes in the guidelines and principles presented by Ibn Qoyyim. The results showed that Ibn Qoyyim emphasized the importance of building a good relationship between parents and children, educating children in the right way, setting a good example, and providing Islamic religious education to children. This research shows that the guidelines and principles presented by Ibn Qoyyim in the book Tuhfaul Maudud bi Ahkamil Maulud are very relevant in shaping the character of early childhood